"Critical Insights into the Therapeutic Potential of Piccha Basti" - Chaudhary, Bhoomika; Singh, Sarvesh Kumar; Rajoria, Kshipra; Bishnoi, Vimla (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Panchakarma( five basic therapeutic procedures in Ayurvedic medicine) therapies, integral to Ayurvedic management, include Basti( medicated enema), targeting Vata imbalances. Piccha Basti, a subtype, employs a standardized blend of honey, raw sugar, clarified butter, medicinal paste, and herbal decoction. It addresses gastrointestinal disorders like diarrhoea and inflammatory bowel disease.Method: The study reviewed classical Ayurvedic texts including Brihatrayee and Laghutrayee and conducted a comprehensive search across various databases and journals such as PubMed, JAIM, ResearchGate, etc. for information on "Basti" and "Piccha Basti". Individual constituent drugs of Piccha Basti were also investigated. Relevant articles were critically analyzed to draw conclusions.Result: Basti( medicated enema), administered rectally, targets the colon, primarily affected by Vatadosha in classical texts. It acts on Vatadosha, Pitta, and Kaphadosha, maintaining equilibrium. The Virya(potency) spreads systemically, exhibiting local and systemic effects. Picchabasti constituents, predominantly Madhur(sweet), Tikta(pungent), and Kashaya(astrigent), possess properties like Picchil( viscous), Sangrahi ( absorbent), Raktashodhaka ( hemostatic), Shonitasthapana ( blood-staunching), Vranaropana ( wound-healing), and Shothahara ( antinflammatory), expediting gut healing. Picchil( viscous) property protects the gut mucosa, while the Sangrahi( absorbent) property regulates stool consistency. Raktashodhaka ( hemostatic) and Shonitasthapan( blood-staunching) properties control bleeding, and Vranaropaka karma ( wound-healing) aids ulcer healing.Conclusion: In Ayurvedic literature, Piccha Basti is lauded for its therapeutic efficacy in treating conditions such as Atisara (diarrhoea), Pravahika (dysentery), and Jirna Grahani (inflammatory bowel disease, IBD). Upon reviewing numerous articles detailing the constituents of Piccha Basti, it has been concluded that these components possess specific chemical constituents that exert a targeted effect on inflammatory bowel disease.